Overview of Foreign Language Learning from Fiki Naki: Efforts to Find Alternative Concepts and Methods for Arabic Learning in the Digital Age - Samin, Saproni Muhammad; Dakhilullah, Tengku Muhammad Dafa; Sanjaya, Malvin (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to describe the concepts and methods of learning foreign languages from Fiki Naki (FN) in the digital age. This research is qualitative descriptive research. The data collection method used in this study is Grounded Theory. Data collection used Library research instruments or Visual Material Review. The research library used eight YouTube videos of interviews with FN and FN's answers to several questions from his fans and used other media sources. The data analysis uses four stages: Codes, Sub-Categories, Categories, and Theory. This study concludes that the FN learning model is suitable for adaptation to foreign language learning to use a foreign language in simple conversation with a native speaker of the target language, not for academic purposes. The concept of learning FN consists of two: psychological and non-psychological. Psychological learning concepts include Learning by fun, high determination and consistency, confidence in using Language, and Self-Regulated Learning. The concepts of non-psychological Learning include Autodidact, intensive Learning, direct language practice, imaginary conversation with oneself and practice it with native speakers, mastery of vocabulary and phrases with keyword strategies, and effective use of online media. At the same time, the learning method that FN uses is a communicative method with several learning techniques, including a focus on listening and speaking skills, using Mnemonic techniques in vocabulary mastery, and conjugation mastery techniques. The novelty of this research is the description of FN's foreign language learning concepts and methods in self-taught foreign language learning. The researchers recommend analyzing and implementing FN's concepts and learning methods in learning Arabic as a foreign language.